The Application of Training Methods and The Influence of Achievement Motivation in Increasing The Speed of Karateka - Jujur Gunawan Manullang; Ilham Arvan Junaidi; Widya Handayani (Universitas PGRI Palembang, 2023)
This study aims to determine the effect of training methods and achievement motivation on the results of karateka karate speed at PGRI Palembang University. The method used in this study is quasi-experiment. The subjects in the study were 37 karateka of PGRI Palembang University. The instrument used in data collection for this variable is the Likert scale model questionnaire. The data analysis technique in this study was with two-track Analysis of Variance (ANAVA) and continued with the Tukey Test. From the results of data analysis shows that there is a difference in the influence of training methods between groups with circuit training methods and interval training is accepted, because the calculation results show Fcalculate = 6.99 > Ftable = 4.05 and there is an interaction between the training method and Achievement Motivation with Speed accepted, because the calculation results show that Fcalculate = 41.77 > Ftable = 4.05.